2020
DOI: 10.1021/acs.langmuir.9b03975
|View full text |Cite
|
Sign up to set email alerts
|

Photothermal Transduction Efficiencies of Plasmonic Group 4 Metal Nitride Nanocrystals

Abstract: The photothermal transduction efficiencies of group 4 metal nitrides, TiN, ZrN, and HfN, at λ = 850 nm are reported, and the performance of these materials is compared to an Au nanorod benchmark. Transition metal nitride nanocrystals with an average diameter of ∼15 nm were prepared using a solid-state metathesis reaction. HfN exhibited the highest photothermal transduction efficiency of 65%, followed by ZrN (58%) and TiN (49%), which were all higher than those of the commercially purchased Au nanorods (43%). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…The greater lattice heating in TiN and ZrN emphasizes the potential of these materials for photothermal applications and this result is consistent with recent findings of photothermal transduction efficiency of ZrN > TiN > Au. [ 24 ]…”
Section: Fluence‐ and Pump Wavelength‐dependent Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The greater lattice heating in TiN and ZrN emphasizes the potential of these materials for photothermal applications and this result is consistent with recent findings of photothermal transduction efficiency of ZrN > TiN > Au. [ 24 ]…”
Section: Fluence‐ and Pump Wavelength‐dependent Responsementioning
confidence: 99%
“…[ 1–9 ] Titanium nitride (TiN), zirconium nitride (ZrN), and other plasmonic nitrides such as hafnium nitride (HfN) and tantalum nitride (TaN) are particularly attractive due to their high melting points that bolster stability at higher ambient temperatures [ 10–12 ] and/or under higher laser irradiation intensities, [ 13–16 ] in addition to their mechanical hardness [ 17,18 ] and complementary metal‐oxide‐semiconductor compatibility. [ 19–21 ] Recent work has demonstrated that TiN shows strong local heating compared to Au, [ 22–24 ] which may be exploited for photothermal therapy, [ 25,26 ] shape‐memory effects, [ 27 ] thermochromic windows, [ 28 ] photoreactions, [ 29–32 ] heat transducers or thermophotovoltaic materials, [ 22,33–37 ] or photodetection. [ 38 ] Implicit in these observations and devices are very different optical responses of metallic nitrides compared to gold—the most similar classical plasmonic material—particularly with regard to the dissipation of heat.…”
Section: Introductionmentioning
confidence: 99%
“…40 The plasmonic response translates in a highly efficient conversion of sunlight into heat, an effect that has been used for water evaporation and desalination. [41][42][43][44] The position of the LSPR of TiN in the infrared region makes it suitable for photothermal therapies or plasmon-induced photocatalysis. 45 Given the optical properties of the group 4 metal nitrides, they are an attractive alternative for gold NCs.…”
Section: Group 4 Metal Nitridesmentioning
confidence: 99%
“…This very relaxation of the high energy carriers also helps stimulate heating of the solid structures involved. This fits the paradigm of photocatalysis as hot electrons can be utilized for various effects from local heating of particles and reactants to photochemistry, photodesorption, and controlled chemical reactions [ 46 , 47 , 48 , 49 ]. The discoveries of photochemical water splitting on TiO 2 electrodes using ultraviolet light [ 50 ], surface-enhanced Raman spectroscopy (SERS) [ 51 ], and femtochemistry studies on single-crystal metal surfaces [ 52 , 53 , 54 , 55 ] served as foundational steps towards current interest in the utilization of hot electron induced chemical reactions on photoexcited metal surfaces, more precisely identified as plasmonic hot electron photocatalysis.…”
Section: Introductionmentioning
confidence: 99%